Spatial and Temporal Change Assessment in Land Surface Temperature of Lahore using GIS and Remote Sensing Techniques: Spatial and Temporal Change Assessment in Land Surface Temperature - u-Minallah, Muhammad Nasar (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
This study is an attempt to evaluate Land Surface Temperature (LST) variations of Lahore, a metropolitan city of Pakistan. LST have wide-ranging application viz; global climate change, urban climate, evapotranspiration, hydrological cycle and environmental studies. Therefore, Spatio-temporal assessment of LST variation is becoming vital to recognize the contributing factors and corresponding magnitude of contribution to the variation using GIS and remote sensing techniques. This study employed the radiative transfer method in assessing Spatio-temporal LST change using multi-temporal imagery acquired by Landsat 5 TM and Landsat 8 TIRS satellite data, for the year 1990 and 2015, respectively. Thermal infrared images of Landsat satellite revealed its suitability in monitoring temporal change in LST. The results indicated that high mean LST was recognized in the areas of Shalamar town, Gulberg town, Data Ganj Baksh town and Ravi town. On the other hand, the low mean LST was observed in the areas of Aziz Bhatti town, Samanabad town, Wagha town and Iqbal town in 1990.The results further showed that the areas of Gulbarg town, Wagha town, Shalamar town, Ravi town, Nishter town and Iqbal town, had been warmer in the year 2015 than the year 1990. It was assessed that in the areas of Aziz Bhatti town, Nishtar town and Wagha town, there were no urbanization and urban development. Therefore the lowest LST was measured in the year 1990. However the expansion and urban development of Lahore in these areas increased surface radiant temperature and they reflect highest LST assessed in 2015. The present study explores the suitability of employing GIS and satellite remote sensing techniques in finding out the spatial and temporal temperature change to achieve accuracy in terms of urban planning, decision and policy making for sustainable urban environment of Lahore